Analysis of Factors Affecting Financial Management Behavior - Yandi Suprapto; Santi Yopie (Journal of Global Business and Management Review, 2019)
The purpose of this study is to determine the effect of risk profile, asset familiarity, investment objectives, investment awareness, and portfolio management on investment behavior. The method of collecting data using a questionnaire aimed at the people of Batam. A total of 100 questionnaires were collected and then processed using SPSS. The study continued with testing the validity and reliability. For testing the hypothesis the author uses multiple linear regression analysis. From this study it can be concluded that risk profile, asset familiarity, investment objectives, investment awareness, portfolio management have a significant positive effect on investment behavior. Overall the independent variable can explain the dependent variable by 51.8% while the rest is influenced by other variables outside the study.